HUBUNGAN PERAN ORANG TUA TERHADAP PRESTASI HAFALAN AL-QUR’AN DI SD ISLAM AL MUSTARIH KOTA BOGOR - Yal Robiyansyah; Siti Sabrina Rachmawaty; Abdul Kodir; Septi Nur Azizah; Muhammad Zahid Mukhlis (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2023)
Memorizing the Al-Quran is an activity to remember the reading of the Al-Quran, but this activity is not an easy thing, especially for students. The process of memorizing the Al-Quran is individual and requires consistency, patience, and sufficient support to improve memorization and maintain it in each individual's long-term memory. However, there are still many students who have not achieved the memorization target according to school regulations. Apart from that, it can be seen that some students are less enthusiastic about it. This is supported by the role of parents who seem less responsive in dealing with various obstacles and complaints experienced by students. Therefore, to overcome these problems, the researcher wanted to see the relationship between the role of parents and the achievement of memorizing the Al-Quran by students at Al Mustarih Islamic Elementary School, Bogor City. In this way, researchers will provide a solution by measuring the extent to which students' achievement in memorizing the Al-Quran has increased, as well as involving parents in motivating students. The results of the research show that the achievement of memorizing the Al-Qur'an in Classes III and IV of Al Mustarih Islamic Elementary School is classified as moderate with a percentage of 75.70% as many as 81 people, which means that the achievement of memorizing the Al-Qur'an obtained a sufficient score, namely 88-95. Meanwhile, the role of parents with a percentage of 57.94% was 62 out of 107 people, which means that the role of parents has been to help their children in memorizing the Al-Qur'an. Apart from that, there is a positive relationship with the product moment correlation value of 0.367 at a low interpretation value between 0.20-0.40 and the coefficient of determination test with a contribution of 13.5% while the rest is influenced by other variables. So, Ho is rejected and Ha is accepted.